Effect of microwave irradiation power on the bioactive compound of essential oil from indigenous herb, Physalis angulata L. using Solvent free microwave extraction: article - A Razak, Muhammad Faiz; Che Radzi, Nurhaslina (2020)
Physalis angulata L. is an herbal plant from the Solanaceae plant family and it have been used mainly in the medical purpose. The demand for a natural source to replace the usage of synthetic source for antibiotic. The antibiotic come from the bioactive components of the plant is obtained by using extraction process and irradiation microwave power is one of the affecting factors to the composition of the extracted product. The objective of this study is to investigate the effect of different irradiation power and extraction time on the bioactive compound. The essential oils from Physalis angulata L. was extracted by using Solvent Free Microwave Extraction (SFME). The essential oil of Physalis angulata L. was obtained with five differences power (270W, 360W, 450W, 540W, 630W) of irradiation power using a domestic microwave oven with wave frequency of 2.45GHz. The result from GC-MS show the present of 23 compound in the essential oil and the suitable irradiation microwave power for the extraction is 450W with the extraction yield of 0.4787%. These results indicated that the used of high irradiation microwave power more than the suitable value will affect the yield of Physalis angulata L. essential oil